Analisis Pengendalian Kualitas Produk Sanitasi Kloset Duduk Tipe CW 53 J Menggunakan Metode Statistical Process Control (SPC) PT Surya Pertiwi Nusantara - Adam Ryan Febrian, Muhamad; Siti Muhimatul Khoiroh (Fakultas Teknik UMRI, 2024)
One of the products produced by PT Surya Pertiwi Nusantara, namely the seat-type toilet or called CW 53 J, is one of the products that is relatively often produced among various other products that are made only when there is an order (make by order). From the production of CW 53 J often found defects or defects in quality control, the damage varies from small holes in various parts of the body, body cracks, body lack or inappropriate shape, peeled body, body dust etc. Many factors affect the success of production, but there are factors that can be controlled and cannot be controlled. The method in this study is to use seven tools. Seven tools are 7 tools used to control the quality of a product, including: chek sheet, cause and effect diagram, pareto diagram, control map diagram, spread chart, flow chart and histogram .